A Total quality management study at the University of the Philippines Institute for Small Scale Industries - Botuyan, Mary Jean E.; Pardinas, Michael D.; Rivera, Maria Ruby M.; Salangad, Christine C.; Zarate, Maria Therese Laarni L. (College of Engineering, 1993)
A Total Quality Management Study was conducted at the University of the Philippines Institute for Small Scale Industries (ISSI) using two of the modules of the ISO 9000 series. These are ISO 9001 (Quality Systems - Model for Quality Assurance in Design/Development, Production, Installation and Servicing) and ISO 9004 (Quality Management and Quality System Elements - Guidelines) because these were the only ones seen suitable in designing an ideal system for a service oriented organization like ISSI. The ideal system was first designed before coming up with a structured documentation and analysis of the current system. The design contained all applicable quality management elements prescribed in the two ISO modules. These elements became the bases in evaluating how the present system undergoes a transformation towards the ideal system. Comprehensive comparisons of the two systems are tabulated in the following pages. The study culminated with the formulation of the program implementation. This program provided how the top management would metamorphosize to an efficient and effective organization.